Exploring Hindu Philosophy, by Ankur Barua - Ram-Prasad, Chakravarthi (Religions of South Asia, 2023)
Exploring Hindu Philosophy, by Ankur Barua. Sheffield: Equinox, 2023. xi + 183 pp., £22.95 (pb). ISBN 9781800502697 (hb), 9781800502703 (pb).